Analysis of the Effect of Entrepreneurship Education and Entrepreneurial Mindset on Entrepreneurial Skills using use of Social Media as a Mediator Variable at SMKN & SMKS with Marketing Expertise Programs in Mojokerto Regency - Nurul Wahyuni; Ludi Wishnu Wardana; Titis Shinta Dhewi (East Asian Journal of Multidisciplinary Research, 2023)
Business is often discussed in all forums and media, as evidenced by many teaching methods, and business is now a required course in many higher and basic universities (Lockma & Schirm, 2020). In this research, we use several methods using partial least squares equation modeling (PLS-SEM) to estimate and confirm the given hypotheses. This study uses Google Forms to collect information on employment and secondary school students in Mojokerto Regency. The respondents to this study are 346 respondents from three schools targeted for this study. Entrepreneurship education has therefore been shown to be incapable of explaining social media use or entrepreneurial skills. However, theories of entrepreneurship can explain social media use and entrepreneurial skills. Additionally, market perception will have a greater impact on the market if it is improved using social media as an indicator. At the same time, although business education is strong using social media as an intermediary, it does not appear to have a greater impact on the ability to do business.